(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The purpose of the study was to validate the Slovenian version of the ATEMPT questionnaire, a 6-item tool to assess adherence to physical activity (PA) among people with widespread non-cancer chronic pain (WCP). To our knowledge, this is the only validated questionnaire in Slovenian language to measure adherence to PA among patients with WCP. Methods: The sample consisted of 107 patients with WCP (female = 102; 95.3%) with a mean (standard deviation) age of 56 (8) years. The break between test and retest was median (interquartile range) 8 (0) days. The difference between test and retest for each question and the total score of the questionnaire was calculated using paired samples t-test. Inter-item correlations and correlations between each question and the total score of the ATEMPT questionnaire (i.e. internal consistency) were calculated using the Spearman rank correlation coefficient. Reliability of questions and total score was calculated using intra-class correlation coefficient (consistency) and interpreted according to recent guidelines. Results: Patients reported similar score within each question and in total score between test and retest, with the exception of significantly greater score of the first question at retest (mean difference = +0.32 points, p = 0.003). Correlations between test and retest score for each question and the total score of the questionnaire were all positive, and moderate-to-high and statistically significant (all p < 0.001). Reliability of the ATEMPT questions and total score varied from moderate for Q1 (intraclass correlation coefficient (ICC) = 0.688), Q3 (ICC: 0.701) and Q4 (ICC: 0.700), to good for Q2 (ICC: 0.852), Q6 (ICC: 0.824), and total score (ICC: 0.852). All ICCs were significant (p < 0.001). Conclusion: PA is an important factor in chronic pain management as it has several beneficial effects. Therefore, patients with WCP should engage in regular physical activity. The results suggest that the Slovenian version of the ATEMPT questionnaire is a valid and reliable tool and can be used to assess adherence to physical activity in people with WPC. Support/Funding Source: Research was funded by European Union, NextGenerationEU, and Republic of Slovenia, Ministry of Health as part of the Recovery and Resilience Plan.